ANTI-B CELL THERAPY OF AUTOIMMUNE DISEASES - A. L. Masliansky (SPb RAACI, 2014)
Abstract. Our understanding of the multiple physiological and pathological functions of B-cells continues to expand at a fascinating rate. As pathogenic elements in the development of autoimmune diseases, B-cells have become the focus of new therapeutics. Based on the published data, rituximab, a chimeric monoclonal antibody to CD20, when used in combination with other agents (i.e., cyclophosphamide or methotrexate), appears to be a reasonable treatment option for refractory RA. There are now numerous case reports and small openlabel series using rituximab in many autoimmune diseases, others then RA. While these data must be interpreted with caution, they suggest that rituximab may be a promising addition to the therapeutic armamentarium in these diseases. However, additional controlled trials need to be conducted to confirm clinical efficacy, further define optimal dosage, response rates, comparative long-term efficacy, and treatment algorithm for rituximab in these patients.